Chilean Preservice Teachers’ Metaphors of English Language Assessment (2022)
Abstract The current study identifies and analyzes, through metaphor analysis, the conceptualizations and beliefs preservice teachers of English hold about three different dimensions of the language assessment process: teachers, students, and assessment itself. Forty-nine preservice teachers from the second to the fifth year of their English Teaching Program answered a metaphor questionnaire in which they created a metaphor for each of the three dimensions above. Then, these metaphors were later analyzed using predominantly qualitative techniques. A metaphoric analysis protocol allowed the metaphors to be coded and sorted based on the participants’ reasoning into the roles participants considered teachers, students, and assessment played in the process of assessment. Findings were organized into three dimensions: teachers’ roles, students’ roles, and the role of assessment. Seven different metaphoric representations of teachers’ roles in assessment were identified, while three were found for students and two for assessment. The present study also revealed that the preservice teachers held varied metaphors regarding the process of language assessment, showing a complex and deep understanding of the purposes of assessment from the role of teachers and students. There is a need for further study to understand why preservice teachers assigned these roles to these agents.